The influence of the administrative-territorial reform on public management mechanisms of the development of the road industry of Ukraine - Tymokha, Anatoliy (Theory and Practice of Public Administration, 2024)
The article examines the influence of the administrative-territorial reform on the transformation of mechanisms of public management of the development of the road industry in Ukraine. The relevance is due to the need to modernize the road infrastructure in the context of European integration aspirations and post-war reconstruction, as well as the decentralization of power, which has caused significant changes in the management system of the industry. The analysis of scientific works devoted to the public management of the development of the road industry was carried out, and the insufficient research of the comprehensive impact of the administrative-territorial reform on the functioning of the industry was revealed.The purpose of the article is to identify and analyze changes in the mechanisms of public management of the development of the road industry under the influence of decentralization, as well as to develop scientifically based recommendations for their improvement.An integrated approach has been applied, combining methodological principles of public management and administration, regional economy, as well as methods of systemic, institutional and comparative analysis.It was established that the administrative-territorial reform caused a redistribution of powers between the central and local authorities in the field of road management, intensified the role of communities in management processes, created conditions for the implementation of innovative approaches, but at the same time revealed a number of problems related to the insufficient institutional capacity of some OTs, risks of deepening regional disparity and coordination difficulties between different levels of government.Recommendations are offered for increasing the institutional capacity of OTG, improving coordination mechanisms and ensuring active participation of the public in managing the development of the road industry.